2016
DOI: 10.1126/science.aad8866
|View full text |Cite
|
Sign up to set email alerts
|

The atmosphere of Pluto as observed by New Horizons

Abstract: Observations made during the New Horizons flyby provide a detailed snapshot of the current state of Pluto's atmosphere. While the lower atmosphere (at altitudes <200 km) is consistent with ground-based stellar occultations, the upper atmosphere is much colder and more compact than indicated by pre-encounter models. Molecular nitrogen (N 2 ) dominates the atmosphere (at altitudes <1800 km or so), while methane (CH 4 ), acetylene (C 2 H 2 ), ethylene (C 2 H 4 ), and ethane (C 2 H 6 ) are abundant minor species, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
205
0
4

Year Published

2016
2016
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 219 publications
(228 citation statements)
references
References 67 publications
19
205
0
4
Order By: Relevance
“…That location was past closest approach along Pluto's dawn flank, and these authors further estimated that this amount of slowing might occur~6 R P directly upstream from Pluto. This indicates a smaller obstacle than anticipated, consistent with the lower than previously expected atmospheric escape rates, which are currently estimated to be~1 × 10 23 N 2 s À1 and~5 × 10 25 CH 4 s À1 from NH occultation measurements [Gladstone et al, 2016]. We note that these values are still highly uncertain with estimated uncertainties of about an order of magnitude for N 2 and a factor of 3-4 for CH 4 .…”
Section: à3supporting
confidence: 84%
See 3 more Smart Citations
“…That location was past closest approach along Pluto's dawn flank, and these authors further estimated that this amount of slowing might occur~6 R P directly upstream from Pluto. This indicates a smaller obstacle than anticipated, consistent with the lower than previously expected atmospheric escape rates, which are currently estimated to be~1 × 10 23 N 2 s À1 and~5 × 10 25 CH 4 s À1 from NH occultation measurements [Gladstone et al, 2016]. We note that these values are still highly uncertain with estimated uncertainties of about an order of magnitude for N 2 and a factor of 3-4 for CH 4 .…”
Section: à3supporting
confidence: 84%
“…Ultimately, we hope to be able to use SWAP data to differentiate between CH 4 and N 2 , which are expected to have the highest escape rates. Here we calculate the heavy ion moments ( Figure 6, thick lines) assuming that all ions are CH 4 , which are currently expected to dominate N 2 [Gladstone et al, 2016] and numerically integrate the observed distributions. We assume that the peak of a symmetric distribution is in the SWAP FOV and the 13.3 km s À1 tailward motion of NH is accounted for.…”
Section: Pluto's Heavy Ion Tailmentioning
confidence: 99%
See 2 more Smart Citations
“…Both atmospheres also contain other minor species, such as CH 4 , CO, and various hydrocarbons Gladstone et al 2016), and both atmospheres are observed to have clouds and/or haze layers (Yelle et al 1991(Yelle et al , 1995. At Triton, observations of ion layers below the main ionospheric peak could be evidence of the presence of metallic ions introduced from meteoric ablation (cf.…”
Section: The Giant Planets; Titan Triton and Plutomentioning
confidence: 99%